Islam dan Globalisasi : Pengaruh Globalisasi Dalam Penyampaian Dakwah Islam - Hidayat, Rahman; Nurfadilah, Muhammad Rifa; Azzam, Fariz Abdul; Syakira, Azka Rizqiya; Jamil, Gita Wahidah; Nuraini, Intan; Muhyi, Asep Abdul; Chodijah, Siti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explain how Muslim societies respond to globalization issues, particularly in the context of preaching through the medium of film. One of the cases raised was a Malaysian production bid’ah-themed film that was being widely discussed, showing that preaching is now not only done orally, but also through the visual medium. Globalization and technological developments have facilitated social and religious activity, including in the spread of preaching. This study uses a qualitative method with a thematic interpretation (maudhu’I interpretation) approach, namely by tracing the relevant verses of the Qur’an using keywords, then analyzed through translation, interpretation, asbabun nuzul, and the meaning of their content. Data sources were obtained from reliable journals, books, and references. The results of this study are expected to provide an overview of how Islam makes sense of globalization as well as the role of technological media, such as film, in communicating the values of preaching effectively and contextually.